2008
DOI: 10.1128/aac.01183-07
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gene Expression in Human Macrophages Treated with the Anti- Leishmania Pentavalent Antimonial Drug Sodium Stibogluconate

Abstract: Within the mammalian host, Leishmania donovani is an obligatory intracellular protozoan parasite that resides and multiplies exclusively in the phagolysosomes of macrophages. Leishmania control relies primarily on chemotherapy, with the mainstay being pentavalent antimony (SbV) complexed to carbohydrates in the form of sodium stibogluconate (Pentostam) or meglumine antimoniate (Glucantime). The mode of action of SbV is still not known precisely. To explore the effect of SbV on macrophage gene expression, a mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…Similar results have been reported for the THP-1 human macrophage cell line and confirmed in human MDMs, suggesting that Sb V induces oxidative stress in human macrophages (20). In our study, overexpression of the CAT, GPX2, HMOX1, and TRX genes confirms the effect of Sb V and possibly Sb III in inducing oxidative stress.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results have been reported for the THP-1 human macrophage cell line and confirmed in human MDMs, suggesting that Sb V induces oxidative stress in human macrophages (20). In our study, overexpression of the CAT, GPX2, HMOX1, and TRX genes confirms the effect of Sb V and possibly Sb III in inducing oxidative stress.…”
Section: Discussionsupporting
confidence: 78%
“…In those studies, antimony compounds, as well as Leishmania infection, were demonstrated to modulate the expression of the GSR gene, which is involved in the reduction of glutathione, and that of the ABCB6 and SLC7A11 genes, which encode drug transporters involved in drug distribution or drug reduction in human macrophages (20,22). We also found upregulation of genes involved in the glutathione biosynthesis pathway, antioxidant defense, and drug transporters of the ABCB family, highlighting the expression levels observed for GSTP1, GSS, TRX, and ABCB5.…”
Section: Discussionmentioning
confidence: 99%
“…THP-1 cells were grown at 37°C and 5% CO 2 in RPMI 1640 supplemented with 10% iFBS, 2 mM glutamate, 100 U/ml penicillin, and 100 g/ml streptomycin. Cells, at 3 ϫ 10 4 /well in 96-well plates, were differentiated to macrophages with 20 ng/ml of PMA treatment for 48 h followed by 24 h of culture in fresh medium (10). The cellular toxicity of all compounds was determined using the colorimetric MTT-based assay (9), as described previously for Leishmania promastigotes, except for the incubation temperature, which was 37°C in this case.…”
Section: Methodsmentioning
confidence: 99%
“…Drug transporters at the host cell level have been linked to clinical responses to antimonial treatment and drug resistance (10,11,27). Modulation of gene expression profiles by SSG has also been demonstrated in vitro, and increased levels of glutathione were measured in SSG-treated cells compared to untreated host cells (28). It is possible that differences in the response to oxidative stress, production of cytokines, expression of drug transport- ers, or a combination of these factors between different host cells account for the host cell-dependent phenotype of antimonial drug action.…”
mentioning
confidence: 99%